Mediating Gender Diversity in Digital-Age Teacher Readiness - Dharma, Panji Vesaka; Wulandari, Siti Sri (Perspektif Ilmu Pendidikan, 2025)
This research endeavors to empirically examine the mediating role of the gender diversity issue in influencing the effect of communication skills and technology utilization on readiness for becoming a teacher. The study targeted final-year education students at the Faculty of Economics and Business (FEB), Universitas Negeri Surabaya (UNESA). A quantitative explanatory approach was employed, utilizing the Structural Equation Modeling based on Partial Least Square (PLS-SEM). Data were systematically collected via questionnaires administered to a sample of 132 respondents, determined using a proportional purposive sampling technique based on the criteria of having completed the teaching practice program and having an interest in becoming a teacher. It was established that both communication skills and technology utilization directly and positively impact readiness for becoming a teacher. The key finding centers on the mediating variable, the gender diversity issue, which proved to partially and significantly mediate the effect of communication skills and technology utilization on teacher readiness. This suggests that the technical and communicative competencies of prospective teachers become more effective in enhancing readiness when fortified by sociocultural awareness and sensitivity toward gender diversity issues. The conclusion derived from this study is that developing professional teacher readiness necessitates not only the mastery of pedagogical and technological competencies but also strong integration with inclusive awareness. This research offers a theoretical contribution by positioning the gender diversity issue as a crucial prerequisite that strengthens the dimension of professional readiness in the era of Education 4.0.